Effect of Presponse® on the gain and health of long-hauled, newly arrived calves - F.K. Brazle (Kansas Agricultural Experiment Station Research Reports, 1992)
Five hundred mixed-breed steer and bull calves (246 lbs) were divided into two treatment groups, with one group receiving a new Pasteurella haemolytica vaccine (Presponse®) at arrival. There was no difference between groups in terms of gain, mortality, or morbidity during the 32-day receiving study. The Presponse group required fewer (P<.09) medication days per animal purchased, resulting in 1.68 less drug cost per head than the control group.
Keywords: Cattlemen& #x27; s Day; 1992; Kansas Agricultural Experiment Station contribution; no. 92-407-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 651; Beef; Stocker cattle; Pasteurella vaccine; Presponse; Receiving program; Stress